Twenty Years and Counting: A Look at Waldorf in the Public Sector Using Online Sources - Abigail L Larrison; Alan J Daly; Carol VanVooren (Arizona State University, 2012)
As the number of public Waldorf schools operating in the U.S. continues to grow, there is a need to examine the effectiveness of this approach in the public sector.  This empirical study provides a beginning look at available quantitative and qualitative extant data on public Waldorf schools obtained from state and national websites.  Available data included standardized tests and parent comment boards hosted by the independent source, GreatSchools.org.  Public Waldorf schools were compared to their district standardized test scores in Reading and Math as well as matched comparison schools.  Test score results suggested the Waldorf experience provided a slower academic build-up resulting in poorer test scores in the lower grades followed by higher levels of advanced performance in the 8th grade.  Quantitative content analysis of parent comments supported the idea that public Waldorf is indeed a more holistic approach with greater emphasis on the arts, community and developmentally appropriate practice.  Findings suggest standard measures of school quality may midjudge the effectiveness of holistic education particularly with regards to academics.  Challenges for successfully bringing holistic education into the current cultural-political climate are discussed.